Middle East and North Africa Economic Update, April 2019 : Reforms and External Imbalances - The Labor-Productivity Connection in the Middle East and North Africa - Arezki, Rabah; Lederman, Daniel; Abou Harb, Amani; Fan, Rachel Yuting; Nguyen, Ha (Washington, DC: World Bank, 2019)
World Bank economists expect economic growth in the Middle East and North Africa (MENA) to continue at a modest pace of about 1.5 to 3.5 percent during 2019-2021, with some laggards and a few emerging growth stars. In late 2018, The World Bank called on the leaders of the Middle East and North Africa (MENA) to aim high. We called for a set of aspirational, but attainable, goals in the digital-economy space (Arezki and Belhaj 2018). If the economies of MENA achieve those goals, they will not only have leapfrogged many advanced economies in terms of coverage and quality of cellular and broadband services, they will register notable advancements in digital payments. This installment of the Middle East Economic Update series, published every six months by the MENA Office of the Chief Economist, makes a more subtle point about a slow moving emerging challenge for the region’s economies: reducing macroeconomic vulnerabilities in some economies is inextricably linked to an all-out effort to create an advanced digital economy (the so-called Digital Moonshot) and other structural reforms. The link, surprisingly, is aggregate labor productivity.